PEMBAGIAN HARTA ADAT DAN PROBLEMATIKA PEMBAGIAN DI DESA TAMMANGALLE KABUPATEN POLEWALI MANDAR SULAWESI BARAT - Aminuddin Aminuddin; Emy Emy; Nur Sahdi (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The purpose of this study is to find out about the division of customary property and the problem of division in Tammangalle village, Balanipa subdistrict, Polewali Mandar Regency. This type of research is qualitative descriptive. The data collected is in the form of statements from the subject without the use of numbers. Primary data is obtained directly from sources at the research site, in the form of in-person interviews with the local community. As for the results of research obtained that the division of inheritance in Tammangalle Village is actually in line with Islamic sharia because men get two while women get one. This reason is based on the responsibility of boys is heavier than girls, such as dependents on the needs of children, wives, and relatives. While the daughter before she married all the needs on her are borne by her parents or guardians. However, if she is married, then the responsibility is changed and is assigned to her husband who becomes the head of the family. In fact, even in the village of Tammagelle even in line with islamic teachings but still found problems that often arise such as the law of wills carried out, in the form of oral speech in the presence of probate witnesses addressed to adopted children if there is or "Oral Speech" which in practice has not met the standard of validity of a statement. REFERENCES Hadikususma, Hilman. (2015). Hukum Waris Adat. Cet. VIII; Bandung: Citra Aditya Bakti , Cet 8. Hadikususma, Hilman. (1992). Pengantar Ilmu Hukum Adat Indonesia. Bandung: Mandar Maju. Hajati, Sri, dkk. (2018). Buku Ajar Hukum Adat, Cet. I; Jakarta: Kencana. Instruksi Peresiden No. 1 Tahun 1991 tentang Kompilasi Hukum Islam. Kementerian Agama. (2012). Al-Qur’an dan Terjemahan. Jakarta: Sinergi Pustaka Indonesia. Muthiah, Aulia. (2015). Hukum Waris Islam: Cara Mudah dan Praktis Memahami dan Menghitung Warisan. Yongyakarta: Pustaka Yustisia. Saebani, Beni Ahmad. (2015). Fiqh Mawaris. Bandung: Pustaka Setia. Simanjuntak, P.N.H. (2005). Pokok-Pokok Hukum Perdata Indonesia. Cet. II; Jakarta: Djambatan. Soepomo. (1993). Bab-bab tentang Hukum Adat, Cet. XIII; Jakarta: Pradnya Paramita. Subekti. (1987). Pokok-Pokok Hukum Perdata, Cet. XXI; Jakarta: Intermasa.